CHALLENGES AND STRATEGIES FOR INCORPORATING GREEN SKILLS INTO TVET PROGRAMS: INSIGHTS FROM INDONESIAN UNIVERSITY PRACTICES - Amal Fathullah; Laili Savitri Noor; Ellyta Ellyta; Suslinawati Suslinawati; Ari Jumadi Kirnadi (International Journal of Teaching and Learning, 2023)
The need for green skills in the workforce has become increasingly evident as the world faces pressing environmental challenges and the transformative impact of the Fourth Industrial Revolution. This abstract explores the challenges and strategies involved in integrating green skills into Technical and Vocational Education and Training (TVET) programs, with a focus on Indonesian university practices. Indonesia, a country with a burgeoning economy, is keenly aware of the importance of sustainability and environmental responsibility. Indonesian universities have embraced the task of equipping students with green skills to meet the demands of a rapidly changing job market. This abstract offers insights into how these universities address the challenges this endeavor poses. The challenges of incorporating green skills into TVET programs are multifaceted, including the need to update curricula, provide relevant training, and foster a culture of sustainability. Moreover, ensuring students are prepared for emerging industries and occupations in a rapidly evolving landscape is a considerable challenge. In response to these challenges, Indonesian universities are implementing various strategies. These strategies encompass curriculum revisions that integrate sustainability principles, hands-on training in green technologies, collaboration with industry partners, and promoting eco-consciousness among students. Universities also invest in research and development to advance green technologies and practices.